Biology of Varroatosis in Bees and Measures for its Control - Shomaxsudov Alisher; Shodmonov Asliddin (American Journal of Biology and Natural Sciences, 2025)
The article provides scientific information on diseases that affect the life activities and productivity of bees. It includes details about the development, progression, and damage caused by diseases, as well as measures for combating these diseases and methods for their prevention.